My proof. We need to show that $a=0$ or $b=0$ for the equation. We have,

$\left( a+b\right) ^{3}=a^{3}+3a^{2}b+3ab^{2}+b^{3}$ (by the binomial theorem)

$=a^{3}+b^{3}$ (by the assumption).

Now, adding $(-(a^{3}+b^{3})$ both sides yields $3a^{2}b+3ab^{2}=0$, i.e., $3ab\left( a+b\right) =0$ (by the distributive law). Since $3ab\left( a+b\right) =0$, $3ab=0$ or $(a+b)=0$, i.e., $a=0$ or $b=0$.

Can you check my proof?

in addition, Let $a$ and $b$ be real numbers. Then $\left( a+b\right) ^{3}=a^{3}+b^{3}$ implies $a=0$ and $b=0$.

So, how can I show this?

  • 6
    $\begingroup$ Let $a = 1$ and $b=-1$. $\endgroup$ – Jacky Chong Oct 5 '16 at 21:50
  • $\begingroup$ I think you have the impose the condition $a, b\geq 0$ or $a, b \leq 0$. $\endgroup$ – Jacky Chong Oct 5 '16 at 21:51
  • $\begingroup$ @SimpleArt I did not understand you. If $a=b=1$ or $a=\sqrt {b}$ then, what can it be? $\endgroup$ – James Ensor Oct 5 '16 at 21:55
  • $\begingroup$ @Kahler No, I just read the problem wrong. Anyways, all the other answers are fine. $\endgroup$ – Simply Beautiful Art Oct 5 '16 at 21:55
  • $\begingroup$ @JackyChong You are right. I should disprove. $\endgroup$ – James Ensor Oct 5 '16 at 21:56

What you are trying to prove is not true. For instance, let $a=1$ and $b=-1$, then $(a+b)^3=a^3 + b^3=0$.

The final conclusion of your attempted proof is incomplete, because $3ab(a+b) = 0$ implies that $a=0$ or $b=0$ or $a=-b$.

The case where $a=-b$ can be eliminated if you restrict $a$ and $b$ to be nonnegative. Thus, if $a,b \geq 0$ your proof is correct.

  • 1
    $\begingroup$ I am thinking you should restrict $a\times b\ge0$, this allows $a,b$ to be both negative. $\endgroup$ – Simply Beautiful Art Oct 5 '16 at 21:56
  • 1
    $\begingroup$ @Kahler No, it implies $a=0$ or $b=0$: $$\begin{cases}a=0\\b=0\\a=-b\end{cases}$$ $\endgroup$ – Simply Beautiful Art Oct 5 '16 at 22:00
  • 1
    $\begingroup$ @Kahler You can't prove that, because it isn't true. The best you can say is that $a=0$ or $b=0$ or $a=-b$. $\endgroup$ – wgrenard Oct 5 '16 at 22:02
  • 1
    $\begingroup$ Come up with a counterexample. Find two real numbers $a$ and $b$ where $(a+b)^3=a^3+b^3$ but $a$ and $b$ are not both zero. This will disprove the statement. Hint: let $a=0$ and $b$ equal anything else besides zero. $\endgroup$ – wgrenard Oct 5 '16 at 22:04
  • 1
    $\begingroup$ @Kahler You are correct! $\endgroup$ – wgrenard Oct 5 '16 at 22:07

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.